The Quest for God: Rethinking Desire. (July 2019) - Ellis, Fiona
Abstract: How are we to view the nature of desire and its relation to value, humanity, and God? Sartre, Nietzsche, and Levinas have interesting things to say in this context, and they can be understood to be responding in their different ways to two seemingly opposed ways of conceiving of desire, namely, as lack or deficiency (option 1) or as plenitude or creativity (option 2). I clarify, link, and distinguish the relevant conceptions of desire, and give a sense of what it could mean to comprehend desire in either or both of these ways. I question Sartre's insistence that man is a 'useless passion', trace it back to his commitment to a 'lack' model of desire, and argue that this model, as he understands it, stands in the way of the more creative conception which is lurking in the background of his account. There will be a question of whether the atheist is entitled to this creative conception, and I shall challenge his assumption that it becomes available only when theism is overthrown. I shall suggest also that there is something important to be salvaged from the lack model.